Pre-B cell receptor signaling in acute lymphoblastic leukemia - Nahar, Rahul (2009)
B cell lineage ALL represents by far the most frequent malignancy in children and is also common in adults. Despite significant advances over the past four decades, cytotoxic treatment strategies have recently reached a plateau with cure rates at 80 percent for children and 55 percent for adults. Relapse after cytotoxic drug treatment, initial drug-resistance and dose-limiting toxicity are among the most frequent complications of current therapy approaches. For this reason, pathway-specific treatment strategies in addition to cytotoxic drug treatment seem promising to further improve therapy options for ALL patients. In a recent study on 111 cases of pre-B cell-derived human ALL, we found that ALL cells carrying a BCR-ABL1-gene rearrangement lack expression of a functional pre-B cell receptor in virtually all cases. In a proof-of-principle experiment, we studied pre-B cell receptor function during progressive leukemic transformation of pre-B cells in BCR-ABL1-transgenic mice: Interestingly, signaling from the pre-B cell receptor and the oncogenic BCR-ABL1 kinase are mutually exclusive and only “crippled” pre-B cells that fail to express a functional pre-B cell receptor are permissive to transformation by BCR-ABL1.